Application of Edible Coating of Durian Seed Starch Chitosan Composites With Kesum Leaves Extracts on Microbiological Quality And TVB-N of Beef Sausage (Jurnal Ilmu dan Teknologi Hasil Ternak, 2022)
The edible coating is one alternative that has the potential to extend the shelf life of sausages. This study aimed to determine the effect of the type of packaging and the storage times of beef sausages at frozen storage. The study using the factorial completely randomized design (CRD) with two factors. The first factor is the type of packaging (K1: edible coating durian seeds starch-chitosan; K2: edible coating durian seeds starch-chitosan with kesum leave extract; K3: plastic LDPE). The second factor is storage time (L0: 0 months; L1: 1 month; L2: 2 months; L3: 3 months; L4: 4 months) with four replication. The research variable observed was the sausage quality like TPC (Total Plate Count) and TVB-N (Total Volatile Bases). The result showed that the treatment of type packaging, storage time, and the interaction had a very significant effect on TPC with the lowest value K3L0 (2.31 x 104 CFU/g) and the highest value K1L4 (11.79 x 104 CFU/g). And, it had a significant effect on TVB-N with the lowest K1L0 (9.19 mg/N/100 g) and the highest value K1L4 (50.93 mg/N/100 g). Â Edible coating of durian-chitosan seed starch with kesum leaf extract can extend the shelf life of beef sausage for four months at freezing temperature based on the TPC value of 9.65.104 cfu/g and TVB-N value 23.96 mg N/100 g.